Blood Proteomics-Based Detection of Upregulated Lipid Metabolism and Immune Dysfunction in an Elite Adventure Athlete Trekking Across Antarctica. (29th May 2020) - Nieman, David; Groen, Arnoud; Pugachev, Artyom; Simonson, Andrew; Polley, Kristine; James, Karma; El-Khodor, Bassem; Varadharaj, Saradhadevi; Hernández-Armenta, Claudia
Abstract: Objectives: Proteomics when combined with psychological, nutrition, and performance measures may serve as a useful monitoring system for immune dysfunction, training distress, and exercise-induced muscle damage and exhaustion in athletes. Global proteomics monitoring of an elite adventure athlete (age 33 years) was conducted over a 28-week period that culminated in the successful, unassisted 2-month trek across Antarctica (1500 km). Methods: Training distress was monitored weekly using the 19-item, validated Training Distress Scale (TDS). Weekly dried blood spot (DBS) specimens were collected via fingerprick blood drops onto standard blood spot cards. DBS proteins were measured with nano-electrospray ionization liquid chromatography tandem mass spectrometry (nanoLC-MS/MS) in data-independent acquisition (DIA) mode, and 712 proteins were identified and quantified. Results: The participant experienced a decrease of 11.4 kg in body mass during the Antarctica trek. The 28-week period was divided into time segments based on TDS scores, and a contrast analysis between weeks 5–8 (low TDS) and weeks 20–23 (high TDS, last month of Antarctica trek) showed that 31 proteins (n = 20 immune related, n = 14 nutrition related with n = 8 in dual roles) were upregulated and 35 (n = 17 immune related) were downregulated. Protein-protein interaction (PPI) networks and gene ontology (GO) biological process analysis supported an increase in plasma lipoprotein particle remodeling, regulation of lipid transport, retinoid metabolic process, and vitamin transport due to high energy intake (7048 kcal/d). PPI networks also supported a dichotomous immune response. GO terms for the upregulated immune proteins showed an increase in regulation of the immune system process, especially inflammation, complement activation, and leukocyte mediated immunity. GO terms for the downregulated immune-related proteins indicated a decrease in several aspects of the overall immune system process including neutrophil degranulation and the antimicrobial humoral response. Conclusions: These proteomics data support a dysfunctional immune response in an elite adventure athlete during a sustained period of mental and physical distress, high energy intake, and significant loss of body mass while trekking solo across Antarctica. Funding Sources: Standard Process, Inc., Palmyra, WI.